Efektivitas Model Pembelajaran PjBL Melalui Google Form terhadap Motivasi Belajar Siswa MTs - Muhammad Arifky Pratama; Irwandi Irwandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of the PjBL learning model through Google Form on students' motivation at MTsN 1 Bengkulu Selatan. This research method uses a Non-Randomized Control-Group Pretest-Posttest Design. The results showed that the average value of learning motivation in the experimental class was 75.96, while in the control class is 47.87. The p-value obtained is 0.000. In conclusion, using the PjBL model through Google Form significantly influences student motivation than conventional learning. Keywords: Google Form, Learning Motivation, PjBL